The spectrum of mutations predisposing to familial breast cancer in Poland. Issue 12 (26th June 2019) - Cybulski, Cezary; Kluźniak, Wojciech; Huzarski, Tomasz; Wokołorczyk, Dominika; Kashyap, Aniruddh; Rusak, Bogna; Stempa, Klaudia; Gronwald, Jacek; Szymiczek, Agata; Bagherzadeh, Maryam; Jakubowska, Anna; Dębniak, Tadeusz; et al.
Abstract : To optimize genetic testing, it is necessary to establish the spectrum of breast cancer‐predisposing mutations in particular ethnic groups. We studied 1, 018 women with a strong family history for breast cancer (families with hereditary breast cancer; HBC) from genetically homogenous population of Poland, which is populated by ethnic Slavs, for mutations in 14 cancer susceptibility genes. Additionally, we compared the frequency of candidate pathogenic variants in breast cancer cases and controls. Germline mutations were detected in 512 of 1, 018 probands with breast cancer (50.3%), including BRCA1/2 mutations detected in 420 families and non‐ BRCA mutations seen in 92 families. Thirteen BRCA1/2 founder mutations represented 84% of all BRCA1/2‐positive cases. Seven founder mutations of CHEK2, PALB2, NBN and RECQL represented 73% of all non‐BRCA‐positive cases. Odds ratios for hereditary breast cancer were 87.6 for BRCA1, 15.4 for PALB2, 7.2 for CHEK2, 2.8 for NBN and 15.8 for RECQL . Odds ratios for XRCC2, BLM and BARD1 were below 1.3. In summary, we found that 20 founder mutations in six genes ( BRCA1/2, CHEK2, PALB2, NBN and RECQL ) are responsible for 82% of Polish hereditary breast cancer families. A simple test for these 20 mutations will facilitate genetic testing for breast cancer susceptibility in Poland. It may also facilitate genetic testing for breast cancer susceptibility in other Slavic populations and women of Slavic descent worldwide. Abstract : What's new? Poland is a genetically homogeneous population similar to Iceland, currently designing national policies for genetic testing. To define the range of pathogenic mutations, the authors conducted a large analysis of breast cancer susceptibility genes, defining pathogenic mutations in 50.3% families with hereditary breast cancer. They identified 20 distinct founder mutations in six genes that were responsible for more than 80% of all detected mutations; these 20 mutations could be combined in a single genetic test of breast cancer susceptibility in Polish women.